Banjarese Cultural Traditions During Pregnancy and After Childbirth in South Kalimantan: A Semi-Qualitative Descriptive - Palimbo, Adriana; Salmahi, Andi Ummu; Amiruddin, Ridwan; Syam, Aminuddin (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
The matter of inequality in context of health status is reflected in the high differences in maternal mortality rates in several countries. Often health information is ignored because of differences in understanding the needs of women and their families. This becomes a communication barrier between health care providers and families in selecting and making emergency decisions that may arise during pregnancy, childbirth, and the puerperium. This study aims to describe the habits and traditions of women during pregnancy and after childbirth in maternal health care. This research uses descriptive analysis method with a case study approach. The study sample consisted of four postpartum mothers with criteria of normal conditions without complications since the third trimester of pregnancy, and the similarity of Banjar ethnic characteristics. The illustration of the results shows that four research subjects carried out the habits of the prevailing tradition, including self-perception; services received from attendants, places and types of care; taboo on food and medicine; suggestion about food and medicine; and rituals in the form of ceremonies and salvation prayers together with maternal health care from midwives, nurses at midwife clinics and Puskesmas. Our research findings confirm that Banjar people are accustomed to using cultural traditions that are integrated into their families and communities and health care services in available and affordable facilities in the area.